Pemanfaatan Warung Kopi Dalam Meningkatkan Literasi Digital Di Desa Klambir Hamparan Perak - Suhariyanti; Sabrina Aulia Rahmah; Andi Maysarah; Dewi Wahyuni (Jurnal Pengabdian Masyarakat, 2024)
Digital literacy has become one of the essential skills that includes the ability to use technological devices, access information, and understand and use that information effectively. Digital literacy includes various competencies known as computer literacy, information literacy and media literacy. Information facilities in rural areas are usually easily obtained by meetings or gatherings of a number of local residents, for example, coffee shops have long been known as the social center of many communities including in Klambir Village. The coffee shop, named Warkop Bang si X, is often used as a space to discuss, exchange information, and build social networks. The problems faced by partners in Klambir Village, Hamparan Perak District, there is still a gap in digital literacy, especially among people with a less supportive age background, their curiosity is reduced, so that the ability to access, understand, and utilize digital information is ruled out which can actually be a prerequisite for effective participation in various aspects of life, from education to the economy. The solution to the partner's problem is that the service team conducts counseling by utilizing coffee shops as an increase in residents' interest in using digital literacy. This PKM uses socialization and training methods using digital devices (gadgets). This method aims to provide knowledge.